2017
DOI: 10.1016/j.jaci.2017.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Advances and highlights in allergen immunotherapy: On the way to sustained clinical and immunologic tolerance

Abstract: Allergen immunotherapy (AIT) is an effective treatment strategy for allergic diseases and has been used for more than 100 years. In recent years, however, the expectations on concepts, conduct, statistical evaluation, and reporting have developed significantly. Products have undergone dose-response and confirmative studies in adults and children to provide evidence for the optimal dosage, safety, and efficacy of AIT vaccines using subcutaneous and sublingual delivery pathways in large patient cohorts, ensuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 121 publications
4
78
0
3
Order By: Relevance
“…It is widely accepted that the efficiency of allergen‐specific T‐cell responses during allergen immunotherapy correlates with the capability of this therapy for skewing DCs 39. We have shown that PM‐allergoids promote the generation of Th1 and Treg cells in vitro, but also in vivo upon subcutaneous immunization in mice 16.…”
Section: Discussionmentioning
confidence: 82%
“…It is widely accepted that the efficiency of allergen‐specific T‐cell responses during allergen immunotherapy correlates with the capability of this therapy for skewing DCs 39. We have shown that PM‐allergoids promote the generation of Th1 and Treg cells in vitro, but also in vivo upon subcutaneous immunization in mice 16.…”
Section: Discussionmentioning
confidence: 82%
“…29,30 This is a paradigmatic study revealing the importance of the better understanding of the molecular mechanisms driving alum adjuvanticity in the context of allergy, especially in humans, to continue improving allergen vaccine formulations for AIT. Allergoid-mannan conjugates represent a major development in the search of novel vaccine approaches to improve AIT, 6,[9][10][11] and Alum was introduced as a vaccine adjuvant in 1926 by Glenny et al, 31 and since 1937, it is used in AIT. Although there are different adjuvant preparations that can be used in AIT as immunostimulants (ie, mineral salts or TLR-targeting adjuvants) or delivery systems (ie, different types of microand nanoparticles), 11 nowadays most of the subcutaneous vaccines for AIT include alum as adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…Activated basophils are important biomarkers of allergic responses, reflecting specific IgE functional activity. In vitro basophil activation tests (BAT) may be useful in monitoring patients on AIT, by ex vivo measurements of CD63 or CD203c expression, basophil histamine release (BHR) or diamine oxidase (DAO), avoiding the risk of severe allergic reactions with in vivo allergen challenge . However, advances in practical aspects of the test are required for standardization and adaptation for use in routine laboratories.…”
Section: Candidate Biomarkers For Immune Monitoring In Allergen Immunmentioning
confidence: 99%
“…Information that can be obtained from sequence analysis is highlighted vivo allergen challenge. [94][95][96][97] However, advances in practical aspects of the test are required for standardization and adaptation for use in routine laboratories. Due to their sequestration into tissues, mast cells remain difficult to investigate in the context of AIT and immune monitoring.…”
Section: Immunoglobulin Transcriptsmentioning
confidence: 99%